2006
DOI: 10.1093/intimm/dxl091
|View full text |Cite
|
Sign up to set email alerts
|

The 8.1 ancestral MHC haplotype is associated with delayed onset of colonization in cystic fibrosis

Abstract: Major cause of death in patients with cystic fibrosis (CF) is colonization with Staphylococcus aureus and Pseudomonas aeruginosa. The wide phenotypic variation in CF patients suggests that genes other than the cystic fibrosis transmembrane conductance regulator (CFTR) gene modify the disease. The 8.1 ancestral haplotype (8.1AH) in main histocompatibility complex is associated with alterations of the immune response. To study the influence of carriage of 8.1AH on frequency and onset of colonization in CF patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…A recent update on the MHC haplotype project [47] states that the haplotypes selected for the project are ancestral haplotypes, and their haplotypic tree space analyses indicates that these are well conserved and representative of MHC diversity in the European population. Our study and others [13,29,45] One recent report that supports this idea, for example, is the delayed colonization in cystic fibrosis in Caucasian individuals with AH8.1 [13]. It is plausible that natural selection favours survival of a population against prevalent infections [48,49] or environmental challenges so that individuals could survive at least up to a reproductive stage, even if it gradually leads to development of autoimmune disorders at later stages.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A recent update on the MHC haplotype project [47] states that the haplotypes selected for the project are ancestral haplotypes, and their haplotypic tree space analyses indicates that these are well conserved and representative of MHC diversity in the European population. Our study and others [13,29,45] One recent report that supports this idea, for example, is the delayed colonization in cystic fibrosis in Caucasian individuals with AH8.1 [13]. It is plausible that natural selection favours survival of a population against prevalent infections [48,49] or environmental challenges so that individuals could survive at least up to a reproductive stage, even if it gradually leads to development of autoimmune disorders at later stages.…”
Section: Discussionsupporting
confidence: 68%
“…It is associated with several autoimmune diseases [3,[5][6][7], including type 1 diabetes [1,4,8], celiac disease [9], systemic lupus erythematosus [10], common variable immunodeficiency [11], myasthenia gravis [12], immunologic hyperreactivity [5], delayed colonization in cystic fibrosis [13], and accelerated progression to acquired immunodeficiency syndrome (AIDS) [14].…”
Section: Introductionmentioning
confidence: 99%
“…This observation leads to the hypothesis that impaired MHC class II protein receptor expression may interfere with host defence mechanisms and may lead to elevated microbial colonization of the lungs of CF patients. This concept is supported by several other studies on the role of MHC class II molecules in CF, e.g., in Aron et al [12] where they found higher levels of IgE and more frequent Psuedomonas aeruginosa colonization in CF patients with DR7/DQA*0201 haplotype [12] or in Laki et al where they found lower frequency of bacterial colonization in CF with the 8.1 ancestral MHC haplotype [17].…”
Section: Discussionsupporting
confidence: 58%
“…8.1AH appeared to be a good candidate because it is carried by up to one quarter of Caucasians and comprises a cassette of linked alleles that play key roles in the inflammatory response: LTA +252A/G (Lymphotoxin A), TNF−308G/A (Tumor necrosis factor), HSP70-2 + 1267A/G (Heat shock protein) and RAGE−429T/C (Receptor for Avanced Glycation Endproducts). Moreover, 8.1AH has been associated with delayed onset of lung bacterial colonization in CF patients in a small cohort of Hungarian patients [10]. As airway inflammation is a key component inducing CF lung damage, we investigated whether the 8.1AH represents such modifier in European CF patients from France, UK and Germany.…”
Section: Introductionmentioning
confidence: 98%